2016
DOI: 10.1016/j.ophtha.2016.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Progression in the Early Manifest Glaucoma Trial

Abstract: Objective To elucidate the temporal relationship between detection of glaucomatous optic disc progression, as assessed by fundus photography, and visual field progression. Design Prospective, randomized, longitudinal trial. Subjects Three hundred and six study eyes with manifest glaucoma with field loss and 192 fellow eyes without any field defect at the start of the trial, of a total of 249 subjects included in the Early Manifest Glaucoma Trial (EMGT) were assessed. Methods Evaluation of visual field pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 52 publications
2
37
1
1
Order By: Relevance
“…Still, comparing with our earlier published results showing an equal ability to detect progression with monoscopic optic disc photographs and automated perimetry in eyes with preperimetric glaucoma (Öhnell et al. ), it is somewhat surprising that we could not detect a higher proportion of optic disc progressions during earlier stages of manifest glaucoma, with a gradual increase of perimetric progression through more advanced stages of the disease.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Still, comparing with our earlier published results showing an equal ability to detect progression with monoscopic optic disc photographs and automated perimetry in eyes with preperimetric glaucoma (Öhnell et al. ), it is somewhat surprising that we could not detect a higher proportion of optic disc progressions during earlier stages of manifest glaucoma, with a gradual increase of perimetric progression through more advanced stages of the disease.…”
Section: Discussionsupporting
confidence: 51%
“…The disc reading procedure is described in detail elsewhere (Öhnell et al. ). Briefly, the readers were masked to the temporal order of the photographs and all other patient data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…6,12,34,38,47 Recent studies have focused on the comparison between progression identified with NFL or optic disc OCT imaging and visual fields. 12,38,48 Abe et al suggested that in patients with different glaucoma stages, monitoring NFL with spectral-domain OCT gives a higher chance of detection of disease progression in early stages, while VF testing is more relevant in later stages 38 .…”
Section: Discussionmentioning
confidence: 99%
“…1, 2 While the rate of retinal nerve fiber layer thinning does correlate with the rate of functional change, 3 the ability to detect glaucomatous progression using structural measurements alone has been reported to be limited. 46 Since function is an important outcome measure for the patient because it relates to quality of life and activities of daily living, perimetry will remain a necessary clinical management tool for the foreseeable future. 7 Most commonly, this is performed using white-on-white standard automated perimetry (SAP).…”
Section: Introductionmentioning
confidence: 99%